2023
DOI: 10.1101/2023.10.20.563336
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Multilevel gene expression changes in lineages containing adaptive copy number variants

Pieter Spealman,
Carolina de Santana,
Titir De
et al.

Abstract: Copy-number variants (CNVs) are large-scale amplifications or deletions of DNA that can drive rapid adaptive evolution and result in large-scale changes in gene expression. Whereas alterations in the copy number of one or more genes within a CNV can confer a selective advantage, other genes within a CNV can decrease fitness when their dosage is changed. Dosage compensation - in which the gene expression output from multiple gene copies is less than expected - is one means by which an organism can mitigate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 135 publications
(259 reference statements)
0
1
0
Order By: Relevance
“…For instance, Aviner et al (72) demonstrated that the ribosome collisions on mutant Huntington transcript produce a cycle of dysfunction that sequesters eIF5a, thereby depleting it from other transcripts and altering translation of stress-responsive transcripts, in part by misregulating their upstream open reading frames (uORFs). Interestingly, a recent preprint linked yeast gene copy number variation, Ssd1, and uORFs by suggesting that genes whose encoded mRNA abundance is substantially discordant with its protein abundance were more likely to contain uORFs, and that those reading frames were enriched for Ssd1 binding motifs (73). While we were unable to find enrichment of known uORFs among the 218 genes, these findings highlight how the altered regulation of Ssd1 targets could render a specific group of gene duplicates toxic, through direct or indirect effects.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Aviner et al (72) demonstrated that the ribosome collisions on mutant Huntington transcript produce a cycle of dysfunction that sequesters eIF5a, thereby depleting it from other transcripts and altering translation of stress-responsive transcripts, in part by misregulating their upstream open reading frames (uORFs). Interestingly, a recent preprint linked yeast gene copy number variation, Ssd1, and uORFs by suggesting that genes whose encoded mRNA abundance is substantially discordant with its protein abundance were more likely to contain uORFs, and that those reading frames were enriched for Ssd1 binding motifs (73). While we were unable to find enrichment of known uORFs among the 218 genes, these findings highlight how the altered regulation of Ssd1 targets could render a specific group of gene duplicates toxic, through direct or indirect effects.…”
Section: Discussionmentioning
confidence: 99%